The Effectiveness of the Yanbu’a Method and the Bil Qolam Method in Learning to Read the Qur’an for Gen Z Students (at the Mamba’ul Ma’arif Islamic Boarding School in Denanyar Jombang and the Sabilurrosyad Islamic Boarding School in Gasek Malang) - Muslih, Ahmad; Haris, Abd.; Gafur, Abd. (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to determine the effectiveness of two methods of learning to read the Qur’an, namely the Yanbu’a Method and the Bil Qolam Method, on generation Z students in two Islamic boarding schools: Mamba’ul Ma’arif Denanyar Islamic Boarding School Jombang and Sabilurrosyad Gasek Islamic Boarding School Malang. The background of this study is based on the importance of the ability to read the Qur’an correctly as part of religious learning, especially for students in the digital era who face the challenges of understanding and practicing Islamic values. This study uses a qualitative approach with a case study type, and data is collected through observation, interviews, and documentation. Data analysis was carried out using the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The results of the study show that both methods have their own effectiveness. The Yanbu’a Method emphasizes gradual learning and systematic mastery of tajwid, while the Bil Qolam Method emphasizes visual and motor aspects with a direct practice approach. Both are effective in improving the ability to read and write the Qur’an, but the success of each method is highly dependent on the characteristics and learning styles of Gen Z students. It is recommended that teachers can combine the strengths of both methods to achieve optimal results in Qur’an learning that are relevant to the needs of today’s young generation.